An Aggregation‐Suppressed Polymer Blending Strategy Enables High‐Performance Organic and Quantum Dot Hybrid Solar Cells. Issue 19 (13th April 2022) - Liu, Junwei; Qiao, Jiawei; Zhou, Kangkang; Wang, Jingjing; Gui, Ruohua; Xian, Kaihu; Gao, Mengyuan; Yin, Hang; Hao, Xiaotao; Zhou, Zhihua; Ye, Long
Abstract: Solution‐processing hybrid solar cells with organics and colloidal quantum dots (CQDs) have drawn substantial attention in the past decade. Nevertheless, hybrid solar cells based on the recently developed directly synthesized CQD inks are still unexplored. Herein, a facile polymer blending strategy is put forward to enable directly synthesized CQD/polymer hybrid solar cells with a champion efficiency of 13%, taking advantage of the conjugated polymer blends with finely optimized aggregation behaviors. The spectroscopic and electrical investigations on carrier transport and recombination indicate that polymer blends can endow fast carrier transport and less recombination over the single counterparts. Moreover, the blending strategy offers a "dilution effect" for top‐notch photovoltaic polymers with excessively strong aggregation tendency, resulting in moderate feature domain size and surface roughness, which afford fast hole transport and therefore high photovoltaic performance. The effectiveness of this strategy is successfully validated using two pairs of photovoltaic polymers. Accordingly, the relationships between polymer morphology, carrier transport, and photovoltaic performance are established to advance the progress of CQD/polymer hybrid solar cells. Such progress stresses that the utilization of aggregation‐suppressed polymer blends is a facile approach toward the fabrication of high‐efficiency organic–inorganic hybrid solar cells. Abstract : A facile polymer blending strategy is put forward to boost the performance of hybrid solar cells with low‐cost directly synthesized lead chalcogenide colloidal quantum dots. This strategy provides a "dilution effect" for polymers with high aggregation tendency, therefore enabling favorable morphology and fast hole transport. Accordingly, the efficiency of CQD/organic hybrid solar cells is promoted to an impressive value of 13%.